TEACHERS SATISFACTION WITH THE COMMUNITY SERVICE PROGRAM ON LEARNING ASSESSMENT AT SMK NEGERI 8 PALANGKA RAYA - Suandi Sidauruk; Ruli Meiliawati; Agtri Wulandari; Anggi Ristiyana Puspita Sari; Fatchiyatun Ni’mah; Triliyansi; Siska Alvionita (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Learning assessment in Vocational High Schools (SMK) plays a crucial role not only in measuring academic achievement but also in evaluating students’ readiness for the workforce. However, assessment practices at SMK Negeri 8 Palangka Raya still face several challenges, including the dominance of summative assessment, limited use of authentic instruments, and restricted application of technology as mandated by the Merdeka Curriculum. These conditions have resulted in low-quality learning outcome data and less effective remedial strategies. To address these issues, a community service program was carried out in the form of an educational seminar. The program was designed in three stages: preparation (needs analysis, development of materials, and evaluation tools), implementation (seminar sessions and interactive discussions on formative, authentic, and Higher Order Thinking Skills/HOTS-based assessment), and evaluation (a teacher satisfaction survey). Data were collected through a Likert-scale questionnaire and analyzed descriptively. The evaluation results showed an average teacher satisfaction rate of 90,38%, with most indicators scoring ≥92,00%, particularly in material relevance, delivery methods, interactivity, and team professionalism. The lowest scores (84,62%) were found in time adequacy, classroom application of seminar results, and the program’s contribution to solving classroom problems, indicating the need for further support. These findings confirm that the program was effective in strengthening teachers’ competence in learning assessment, although follow-up strategies such as in-depth workshops and practical mentoring are necessary to optimize implementation.